Corpus based translation studies ("Conference on Universal Science Research 2023", 2023)
Recently there has been noticeable growth of corpus based studies which came to light in mid 1990s. Corpus- based linguistics paved the way for better translation studies, broadened the scope of research and introduced learning-friendly patterns for translation scholars. Baker, who first coined the copus-besed study theory, made an assumption about availability of large corpora of both the authentic and translated versions of texts, together with the development of corpus-driven methodology, would enable translators to discover (1993_243) “The nature of translated text as a mediated event of our communication. In this research paper I would point out the types of corpus-based translation studies and its potential benefits for future translation. The term corpora was introduced into the Latin language meaning human body. Now this term is related to collection of written texts or transcribed speech which can serve as a basis for linguistic analogy and description. However,  we should not forget compora had long tradition dating back to medieval times when scientists were curious about its potential benefits for their research.